2023
DOI: 10.37497/esg.v6i1.1573
|View full text |Cite
|
Sign up to set email alerts
|

Proposal For a Method For Feasibility Analysis And Implementation Of SDG In Brazilian Municipalities

Abstract: Purpose: This study aims to propose a method, analyzing the feasibility and implementation of SDGs (Sustainable Development Goals) in Brazilian municipalities, examining the reality of each one. The central question is: what is being done to put the 2030 Agenda into practice in Brazilian municipalities? Methodology/approach: DSR (Design Science Research) was used as a methodological basis, as it allows the creation of artifacts, which, during their development, can build theories that describe, explain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This is an increase of almost 200 million people compared to pre-pandemic levels. Then according to Ben Hassen & El Bilali, (2022); the war may jeopardize the implementation (Ribeiro, Espuny & Hermes ,2023) of the Sustainable Development Goals (SDGs), notably SDG 1 (No poverty), SDG 2 (Zero hunger), and SDG 12 (Responsible consumption and production). Lin et al, (2023) using the general equilibrium trade model on analysis of the potential impacts of the conflict on the global wheat market found that the conflict would lead to a 60% trade drop, 50% soaring wheat prices, and severe food insecurity with above 30% decreased purchasing power for wheat in the most severe scenario, especially for countries that heavily rely wheat imports from Ukraine, such as Egypt, Turkey, Mongolia, Georgia, and Azerbaijan.…”
Section: Global Impactmentioning
confidence: 99%
“…This is an increase of almost 200 million people compared to pre-pandemic levels. Then according to Ben Hassen & El Bilali, (2022); the war may jeopardize the implementation (Ribeiro, Espuny & Hermes ,2023) of the Sustainable Development Goals (SDGs), notably SDG 1 (No poverty), SDG 2 (Zero hunger), and SDG 12 (Responsible consumption and production). Lin et al, (2023) using the general equilibrium trade model on analysis of the potential impacts of the conflict on the global wheat market found that the conflict would lead to a 60% trade drop, 50% soaring wheat prices, and severe food insecurity with above 30% decreased purchasing power for wheat in the most severe scenario, especially for countries that heavily rely wheat imports from Ukraine, such as Egypt, Turkey, Mongolia, Georgia, and Azerbaijan.…”
Section: Global Impactmentioning
confidence: 99%